Revisiting a choq pa bursting shargo (women: the miserable): Feminist critique in Balti folktale - Ahmed, Mairaj; Issa, Muhammad; Mustafa, Muhammad (Journal of Language, Literature, Social and Cultural Studies, 2025)
This study examines the Balti folktale “Choqpa Bursting Shargo” through a feminist lens, focusing on the representation of female characters and their societal roles. The research aims to explore gender roles, major themes, and the portrayal of patriarchal structures in the narrative. It highlights the elements of oppression and the marginalization of women in a male-dominated society, drawing attention to the societal norms that perpetuate gender inequality. The study employs a qualitative approach, utilizing feminist literary criticism to analyse the folktale. The research is based on textual analysis, examining key themes and character interactions to reveal underlying patriarchal ideologies. The methodology involves identifying patterns of gender discrimination and assessing their implications within the broader socio-cultural framework. The analysis reveals that women in the folktale are subjected to systemic oppression and are often portrayed in subservient roles. The narrative reflects the realities of patriarchal norms, illustrating how female identity is suppressed and controlled. The concept of double marginalization is also explored, emphasizing how women face compounded oppression both as individuals and as a collective. In conclusion, the research underscores the significance of feminist readings of folklore in unveiling deep-seated gender biases. The study highlights the continued relevance of such tales in contemporary discussions on gender equality, advocating for a more inclusive and equitable representation of women in traditional narratives.